Early treatment with thiamine and mortality among patients with alcohol use disorder who are hospitalized for pneumonia. Issue 8 (21st June 2022) - Baron, Sarah W.; Yu, Pei‐Chun; Imrey, Peter B.; Southern, William N.; Deshpande, Abhishek; Rothberg, Michael B.
Abstract: Background: The paucity of research linking thiamine treatment with improved outcomes may be driving its underutilization among patients at risk for Wernicke encephalopathy. Objective: To assess relationships of thiamine usage to outcomes of patients hospitalized with alcohol use disorder and pneumonia. Design, Setting and Participants: This is a retrospective cohort study of adult patients hospitalized with pneumonia who also have alcohol use disorder and were treated with benzodiazepines during the initial two hospital days, between 2010 and 2015 at hospitals participating in the Premier Healthcare Database. Exposure: Any thiamine treatment, and, among those treated, high‐dose thiamine treatment, during the initial two hospital days. Main Outcome and Measures: Death on days 3–14 of hospitalization (primary); discharge home; transfer to intensive care unit; length of stay (LOS). We used propensity‐weighted models to estimate treatment effects. Results: Among 36, 732 patients from 625 hospitals, 26, 520 (72.2%) patients received thiamine, with mortality of 6.5% and 8.1% among recipients and nonrecipients, respectively. With propensity score adjustment, thiamine was associated with reduced mortality (odds ratio [OR]: 0.80, 95% confidence interval [CI]: 0.75–0.85) and more frequent discharges to home (OR: 1.10, 95% CI: 1.06–1.14). Other outcomes were similar. Relative to low‐dose thiamine, high‐dose thiamine was not associated with mortality (adjusted OR: 0.99, 95% CI: 0.89–1.10), but LOS was longer (ratio of means: 1.06, 95% CI: 1.04–1.08), and discharges to home were less frequent (OR: 0.92, 95% CI: 0.87–0.97). Conclusion: Thiamine is not reliably given to patients with pneumonia and alcohol use disorder receiving benzodiazepines. Improving thiamine administration may represent an opportunity to save lives in this high‐risk group of inpatients.